PARTISIPASI MASYARAKAT DALAM PEMBERDAYAAN KAMPUNG PELANGI DI KOTA SEMARANG - Jauhari, Achmad Fatchul; Astuti, Puji (Journal of Politic and Government Studies, 2018)
The city is always identical with rapid growth because the city becomes a destination for people to migrate either to live, to work, or to study. The rapid flow of urbanization causes the growth of the urban population to increase very rapidly causing high levels of population density. Not infrequently the high housing needs that are not supported by the availability of land cause the emergence of illegal settlements are shabby as well as settlements in the area of Mount Brintik Wonosari Semarang. The emergence of a rough illegal area led to the city government Semarang developing Kampung Tematik program, including the colorful thematic village, Kampung Pelangi.This research is intended to know the form of community participation in the empowerment of rainbow villages and the results of the empowerment program. The method used in this study is descriptive-qualitative with in-depth interviews used as the main instrument of research. The results show that Kampung Pelangi Program which was launched in May 2017 has become a new tourism icon in Semarang City. Although the program is initiated by the government, its success is supported by community participation both in the planning stages, the stages of the action and the stages of evaluation. The results of empowerment programs that add value to the community are increasing incomes, increasing awareness and patterns of community interaction, and the establishment of an organizing system through the formation of tourism conscious groupsFor the sustainability of the Kampung Pelangi program as a tourism village it is necessary to cooperate sustainably both with the government and the private sector either related to maintenance fund and skill improvement needed by the community in order to strengthen the existence of Kampung Pelangi as a tourist destination.Â Keywords : Community Participation, Empowerment, KampungÂ Tematik